1972
DOI: 10.1002/bjs.1800590103
|View full text |Cite
|
Sign up to set email alerts
|

Erosive gastritis: Its Diagnosis, Management, and surgical treatment

Abstract: Total 5 ~~ ~~ 8 2 21.0 I 1 8 7.6 zoo 13.0

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

1973
1973
1982
1982

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…It is difficult to compare series with respect to the proportion of undiagnosed cases, since criteria for diagnosis vary. In some series the authors exclude patients without unequivocal evidence of bleeding; others accept hiatus hernia as a cause, or may diagnose acute erosions on the basis of salicylate ingestion and a negative barium meal (Desmond and Reynolds, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…It is difficult to compare series with respect to the proportion of undiagnosed cases, since criteria for diagnosis vary. In some series the authors exclude patients without unequivocal evidence of bleeding; others accept hiatus hernia as a cause, or may diagnose acute erosions on the basis of salicylate ingestion and a negative barium meal (Desmond and Reynolds, 1972).…”
Section: Discussionmentioning
confidence: 99%
“…For a long time erosive gastritis was not considered to be diagnosable radiographically [1,2]. Recently, several investigators [3-6] using the double-contrast technique demonstrated erosions in a number of patients having symptoms of digestive disease.…”
Section: Discussionmentioning
confidence: 99%
“…For a long time erosive gastritis was not considered to be diagnosable radiographically [1,2]. Recently, several investigators [3][4][5][6] …”
Section: Discussionmentioning
confidence: 99%
“…The operative mortality-rate for the patients with cirrhosis was 53 per cent, or a salvage rate of 47 per cent if one considers that this is a highly selected group of patients (albeit negatively)patients with impaired liver function who had not responded to intensive medical treatment and who were still bleeding at the time of surgery. (Desmond and Reynolds, 1972).…”
Section: Discussionmentioning
confidence: 99%